1999
DOI: 10.1002/(sici)1098-1004(1999)14:3<256::aid-humu9>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of late-life globoid cell leukodystrophy

Abstract: Globoid cell leukodystrophy is an autosomal recessive inherited disease caused by deficiency of the lysosomal enzyme galactocerebrosidase (GALC). Although the severe, rapidly progressing infantile form is the most common, late‐onset forms have been described. We investigated the molecular basis of GALC deficiency in a patient with a late‐life mild form of globoid cell leukodystrophy who survived into the eighth decade. Since material suitable for mutation analysis was no longer available from the proband, her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 16 publications
(22 reference statements)
0
45
2
Order By: Relevance
“…G1873A was present in the heterozygous form in the patients and in one parent but not in controls, suggesting its close association with Krabbe disease. However, expression studies have demonstrated the negative effect of Val550Gly but not Ala625Thr on GALC activity [5,6], suggesting that this latter sequence variant is a polymorphism in tight linkage with Val550Gly (also in the patient described in [6] the two-sequence variants are on the same allele) rather than a causative mutation of GLD.…”
contrasting
confidence: 50%
See 2 more Smart Citations
“…G1873A was present in the heterozygous form in the patients and in one parent but not in controls, suggesting its close association with Krabbe disease. However, expression studies have demonstrated the negative effect of Val550Gly but not Ala625Thr on GALC activity [5,6], suggesting that this latter sequence variant is a polymorphism in tight linkage with Val550Gly (also in the patient described in [6] the two-sequence variants are on the same allele) rather than a causative mutation of GLD.…”
contrasting
confidence: 50%
“…In particular, the T1637C-Ile546Thr polymorphism which may decrease GALC activity [1], was present in 41 % of GLD alleles and 45 % of 60 control alleles. This suggests that in our patients, differently than in other cases [7], mutations do not occur preferentially in the 1637C allele.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The R168C (502C→T) substitution associated with a large deletion (502/del) in the GALC gene has been found at high frequency, together with many mutations in LO-GLD in the allele that carries the 1637C (T546) substitution in Cau- (Rafi et al 1995;Luzi et al 1996;Gasperi et al 1996). However, neither R168C (502C→T), nor a large deletion were found in our patients; the T546 substitution was present in only one allele of patient NG (Fig.…”
Section: G270d Mutationmentioning
confidence: 99%
“…The patient was found to be heterozygous for two previously reported mutations: G > A at cDNA position 809 (G270D) and 1026del10. The first mutation, G > A at cDNA position 809 (G270D), has been identified previously in other patients with adult-onset KD [3,6,14]. The second mutation, previously identified in another Italian patient with infantile KD [14], consists of a 10 basepair deletion starting in exon 10 at nucleotide 1026.…”
mentioning
confidence: 99%